Crizotinib (PF02341066) as a ALK /MET inhibitor— Special Emphasis as a Therapeutic Drug Against Lung Cancer - Nwizu, Tobenna (Drugs Future, 2011)
There are a number of molecular abnormalities that can occur in normal cells to induce a malignant phenotype. Recently, the receptor tyrosine kinase anaplastic lymphoma kinase (ALK) has been shown to have gain-of-function when partnered with different proteins. As an example, on chromosome 2p, with inversion, there is translocation with generation of EML4-ALK tyrosine kinase in lung cancer. In a phase I trial, EML4-ALK patients were selected to determine the response to a potent small molecule tyrosine kinase inhibitor crizotinib (previously identified as PF02341066). Dramatic durable responses were observed with crizotinib at 250 mg twice a day (orally). Interestingly, crizotinib also has activity against MET receptor tyrosine kinase. We have previously shown that MET can be overexpressed, sometimes mutated, or sometimes amplified in lung cancer. Thus, this review will emphasize the characteristics of crizotinib, and detail the clinical experience.